Design And Development of a Graphical User Interface (GUI) In a Medical Dispenser with Smart Card Access - Harun, Nur Fathiah; Hanafi, Dirman (Evolution in Electrical and Electronic Engineering, 2023)
Traditional vending machines serve snacks and drinks, but modern iterations encompass essential supplies. Diverse models emerged to meet various needs. In late 2019, the Covid-19 pandemic prompted global responses. Malaysia enforced movement controls. Strategies, like drive-thru healthcare, aimed to curb gatherings. PKD Pendang, Kedah, adopted this approach but faced queues. The project tackled this with a smart card-accessible medical dispenser linked to patient data. Automation ensured accurate dispensing, secured by authorized smart card access. A user-friendly interface streamlined interactions. Patients could retrieve medication within 10 minutes, enhancing efficiency. Rigorous testing affirmed adherence to this timeline. The prototype effectively addressed dispensing needs, providing timely medication.